APPLICATION OF RECOMBINANT TRIACYLGLYCEROL LIPASE AND CARBOXYLESTERASE ENZYMES FROM Bacillus velezensis STRAIN S3 FOR POLYESTER SURFACE MODIFICATION - Helianti, Is (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Enzymatic polyester surface modification can be performed with lipase and esterase enzymes. In this study, the polyester fabric modification utilized triacylglycerol lipase (TGA) and carboxylesterase (CES) recombinant enzymes. The effect of these treatments was observed by determining the hydrophilicity level, dye absorption level, hydroxyl group measurement, and fiber surface morphology. The results revealed an elevated hydrophilicity level in polyester fabric, followed by dye absorption improvement and carboxyl group increase. The water absorption times required by the fabric based on the results of TGA, CES, comparative lipase, and negative control treatments were 3±0.05 seconds, 3.5±0.07 seconds, 5±0.05 seconds, and 80±11.54 minutes, respectively. Dye absorption test in polyester fabric based on these groups mentioned above were 52±0.5, 58±0.5, 178±0.5, and 2968±290 seconds. The total hydroxyl group measurement in polyester fabric was observed at 30.9±0.09, 30.5±0.05, 28.6±0.09, and 3 meq/100 g. The SEM observation showed that the enzymatic hydrolysis could alter the porous structure and surface of the fibers.